(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This article presents commonly used expressions and idioms found in everyday Uzbek conversations and provides their English equivalents. It illustrates these with clear examples, emphasizing their meanings and usage. In addition, the article compares several well-known English and Uzbek idioms, giving thorough explanations for each.